Dober pripovedovalec z zornega kota poslušalca in raziskovalca - Ivančič Kutin, Barbara (Traditiones (Ljubljana), 2001)
The paper focuses on the notion of good narrator, his or her characteristics, and pecularities, and the perception of such a person by the public on the receiving end, and by a researcher (folklorst). It tries to answer the question whether a narrator who is good according to the public is similarly, viewed by the researcher who is trying to documents a certain folkloristic event. Listed are the opinions of informant6s from the vicinity of Bovec, who in certain cases have themselves acted as narrator's (their statements have been obtained in the course of collecting material for author's M. A. paper). The paper also focuses on author's own experience, as well as on conclussions by Milko Matičetov, a well-known folklorist who conducted his own research of the area several years ago
Keywords: ethnology; etnologija; slovstvena folklora; pripovedništvo; Slovenia; Slovenija